Comparative quantitation of DNA water tracers using OptiQ, Qubit, and Nanodrop. Issue 1 (13th February 2023) - Billington, Craig; Schmidt, Jenelle; Mundle, Robyn; Prenner, Elmar J.; Pang, Liping
Abstract: We have recently developed new synthetic DNA tracers for tracking sources and pathways of contamination in surface water and groundwater. The use of DNA tracers in natural water systems results in substantial and rapid dilutions, thus accurate quantitation of initial DNA tracer concentrations applied is crucial to ensure their successful downstream detections. We compared the sensitivity and accuracy of three portable analytical techniques for quantitation of these DNA tracers: Nanodrop, Qubit, and OptiQ. All three methods were about equally effective when measuring high concentrations of DNA tracers (e.g., for c‐amine DNA tracer 1.54 × 10 5, 1.37 × 10 5, and 1.77 × 10 5 ng/mL for Nanodrop, Qubit, and OptiQ, respectively). However, the fluorescent methods of Qubit and OptiQ were significantly more sensitive at detecting lower concentrations of DNA tracers with limits of detection in the range 0.1–2 ng/mL, compared to 5 × 10 3 ng/mL for Nanodrop. The results of this work will facilitate the practical deployment of DNA tracers for tracking water contamination, and improving freshwater quality. Core Ideas: DNA tracers are a novel technology to track water contamination. DNA tracers are rapidly diluted, so quantitation must be reliable. We evaluated three portable analytical technologies for quantitating DNA tracers. Fluorescent quantitation methods were found to be the most sensitive. These data will facilitate DNA tracer deployment for tracking water contamination.